Desarrollo de una propuesta para la producción de un biocida partiendo de extractos etanólicos de hojas de tabaco (Nicotiana tabacum) en el control de Botrytis cinérea (Pilisboecea). (2020)
The use of plants and fruits that stop the advance of different types of pests has been widely known in traditional cultures and even remains in force in some agricultural sectors. Some of these plants such as chili pepper, paprika, lavender, rosemary and oregano are used to control fungi, mites and insects, nematodes, and weed-type plants, among others. The commercially used methodology requires the spraying of synthetic pesticides such as organochlorine, organophosphate, phenolic and carbamate pesticides; that not only control pests but also contaminate the product itself, such as the soils and waters surrounding the crop, generating the risk of contact with the final consumer. Therefore, this project aims to develop a proposal for the production of a biocide of natural origin starting from ethanolic extracts of tobacco leaves (Nicotiana tabacum) for the control of a fungus (Botrytis cinerea); This project is carried out by reviewing bibliographic material in order to identify the variables that have the greatest effect on the process and also achieve the development of a viable and effective proposal.